2021
DOI: 10.1007/s12020-021-02728-8
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with isolated congenital GH deficiency due to a GHRH receptor gene mutation appear to cope better with SARS-CoV-2 infection than controls

Abstract: Purpose Several interactions exist between the GH/IGF axis and the immune system, including effects on innate immunity and humoral and cellular response. Acquired GH deficiency (GHD) has been recently proposed as a risk factor for severity of COVID-19 infections. However, acquired GHD is often associated to other factors, including pituitary tumors, surgery, radiotherapy, and additional pituitary hormones deficits and their replacements, which, together, may hinder an accurate analysis of the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
(21 reference statements)
0
7
0
1
Order By: Relevance
“…The apparently normal immune function suggests that many immune cells use extrapituitary circuits (local GH/IGFs), independent from the somatotrophic axis. We also found that macrophages from IGHD subjects are less prone to Leishmania amazonensis infection than GH-sufficient controls (73) and that they appear to cope better with SARS-CoV-2 infection than controls (74). Resistance to Leishamnia infection may be one of the reasons for the spread of this mutation in the Itabaianinha region.…”
Section: Sergipe In Gh Researchmentioning
confidence: 55%
“…The apparently normal immune function suggests that many immune cells use extrapituitary circuits (local GH/IGFs), independent from the somatotrophic axis. We also found that macrophages from IGHD subjects are less prone to Leishmania amazonensis infection than GH-sufficient controls (73) and that they appear to cope better with SARS-CoV-2 infection than controls (74). Resistance to Leishamnia infection may be one of the reasons for the spread of this mutation in the Itabaianinha region.…”
Section: Sergipe In Gh Researchmentioning
confidence: 55%
“…Such effect is unlikely, as cognitive function, assessed after the end of the pandemic in Brazil, was excellent in both groups. Furthermore, we have previously shown no difference in the prevalence of anti-SARS-CoV-2 IgM and IgG antibody positivity between IGHD subjects and matched normal stature individuals in October 2020, during the acceleration of the pandemic ( 53 ). The relatively low number of subjects is a limitation of the present study.…”
Section: Discussionmentioning
confidence: 93%
“…Somatropin hormone, thyrotropin, gonadotropin-releasing hormone, and corticotropin-releasing hormone and others impact the RAAS pathway via angiotensin II to modulate blood pressure [ 74 ]. Individuals with isolated congenital GH deficiency due to a GHRH receptor gene mutation appear to cope better with SARS-CoV-2 infection than controls [ 75 ]. Likewise, somatotropin-releasing hormone has been shown to be highly correlated to COVID-19.…”
Section: Discussionmentioning
confidence: 99%